Donor polymer design enables efficient non-fullerene organic solar cells - Zhengke Li (Nature Portfolio, 2016)
In organic photovoltaics, electron acceptors are developed to replace fullerenes, and new donors need to be designed to match these acceptors. Here, the authors show that a polymer with strong temperature dependent aggregation and intentionally reduced crystallinity matches non-fullerene acceptors.